Factors related to the incident respiratory distress syndrome on neonate at the Harapan and Doa Hospital, Bengkulu City - Kusumawardhani, Febry; Nugraheni, Diah Eka; Solihat, Suci; Hartini, Lela; Yuniarti, Yuniarti (Alma Ata University Press, 2025)
Background: Apart from increasing morbidity and motility, respiratory problems in newborn babies are a condition that can result in respiratory arrest and even death. Premature birth, intrapartum problems (asphyxia or shortness of breath at birth), infections, and birth defects are the main causes of newborn deaths worldwide. Newborn babies can die from respiratory distress syndrome, and other causes. It is estimated that respiratory distress syndrome or its consequences cause thirty percent of all newborn deaths. Objectives: This study aims to determine the factors associated with the incidence of respiratory distress syndrome in neonates in the perinatology room at Harapan and Doa Regional Hospital in 2024 Methods: This study used a case control design with a retrospective method. The data taken is secondary data AND The sample for this study were all babies who were treated and diagnosed respiratory distress syndrome in the neonatalogy room at RSU Harapan and Doa in 2023, totaling 65 people. The sample collection technique for the control group was taken using a 1:1 ratio systematic sampling using interval multiples, starting from data number 4 and so on using interval multiples of 4 so that you get the numbering numbers 4, 8, 12, 16 etc. up to the 65th control variable, so that the sample in this study amounted to 130 newborns consisting of 65 case variables and 65 control variables recorded in the register in the perinatalogy room at Harapan and Doa Hospital, Bengkulu City in 2023. Data were analyzed using the Chi-Square test to look for a relationship or correlation between the independent variables (maternal complications, type of delivery, gender, gestational age, birth weight) and the dependent variable respiratory distress syndrome. The level of statistical significance was set at a p value <0.05. Results: The results of this study show that the p-value of maternal complications is p=0.595 (p-value ≥0.05), type of delivery p= 0.074 (p-value ≥0.05), gender p= 0.289 (p-value ≥ 0.05), gestational age p= 0.000 (p-value ≤0.05), birth weight p= 0.000 (p value ≤0.05). Multivariate analysis showed that birth weight was the most dominant factor causing respiratory distress syndrome (OR 5.713; p=0.000).Conclusions: There is a significant relationship between gestational age and birth weight and the incidence of respiratory distress syndrome. However, no significant relationship was found between maternal complications, gender or type of delivery and the incidence of respiratory distress syndrome.